HUMAN RIGHT AKIBAT TINDAKAN DISKRIMINATIF BAGI PENYANDANG DISABILITAS DALAM DUNIA KERJA - Dr. Zainal Abidin Pakpahan, SH, MH (Universitas Labuhanbatu, 2023)
The treatment of discrimination in the world of work for persons with disabilities still occurs in every line of life in companies located in each region, which should receive special treatment as an effort to maximize the respect, promotion, protection and fulfillment of human rights universally and not to be discriminated against. In addition, persons with disabilities always face greater difficulties than non-disabled people due to barriers to accessing public services, such as access to education, health, and employment services so that disability should not be an excuse and obstacle for persons with disabilities to obtain the right to life and the right to maintain their lives and lives because this is a constitutional mandate in Article 28 A and Article 28 I of the 1945 Constitution and other laws and regulations that emphasize the absence of differences and discrimination in employment. This kind of discrimination has been felt by people with disabilities in the world of work that occurs in Indonesia, one of which is the non-acceptance of a person with a disability who is in a wheelchair to become a civil servant in the city of Surabaya in 2005 and this becomes jurisprudence in the Supreme Court of the third person with disabilities filed a lawsuit in the State Administrative Court to the Mayor of Surabaya and the refusal of a person with a disability to re-work in a state-owned enterprise due to a right foot disability so that such treatment and actions constitute discriminatory acts as human rights violations for which they should receive special protection and treatment from their employment rights as persons with disabilities working in informal sector corporate agencies.Keywords: Human Right, Discriminatory, Employment, Company, Disability